2018
DOI: 10.1556/030.65.2018.031
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible silver resistance readily evolves in high-risk clone isolates of Klebsiella pneumoniae

Abstract: Silver is used extensively in both hospitals and outpatient clinics as a disinfectant coating agent on various devices. Resistance to silver was recently reported as an emerging problem in Enterobacteriaceae. Multidrug-resistant high-risk clones of Klebsiella pneumoniae are common causes of serious healthcare-associated infections worldwide posing a serious threat to patients. In this study, we investigated the capacity of both high-risk (CG14/15 and CG258) and minor clone strains of K. pneumoniae to develop r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
9
0
5
Order By: Relevance
“…The small plasmids contained putative virulence determinants. The presence of these systems may contribute to the success of transmission of specific K. pneumoniae strains in the hospital setting or the community 13 , 29 , 30 . Escherichia RCS47 prophage sequences were found on medium and large plasmids in the cluster isolates analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…The small plasmids contained putative virulence determinants. The presence of these systems may contribute to the success of transmission of specific K. pneumoniae strains in the hospital setting or the community 13 , 29 , 30 . Escherichia RCS47 prophage sequences were found on medium and large plasmids in the cluster isolates analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Staehlin and colleagues12 have described a heavy metal homeostasis/resistance island, named as Copper homeostasis and silver resistance island (CHASRI), which was assembled and dispersed within members of Enterobacteriaceae family. Recently, CHASRI was found to be equally distributed in the plasmids and chromosomes of Enterobacteriaceae and was able to provide silver-resistance after mutation in Cus S and/or sil S genes of the CHASRI island 13…”
Section: Introductionmentioning
confidence: 99%
“…MLST analysis showed that silver resistance can be induced within K. pneumoniae strains belonged to both high-risk group (ST11 and ST15) and minor clone groups, which is in line with previous study. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Relative change in the fitness cost of Ag + resistance was determined by growth curves between the susceptible parent strains and the corresponding mutants. 14 …”
Section: Methodsmentioning
confidence: 99%